Maternal β-carotene addition has long-term effects on intestinal health of offspring chicks - Wang, Taiping; Wan, Da; Ren, Tianyu; Tao, Ye; Wu, Min; Zheng, Xin (Frontiers in Microbiology, 2025)
BackgroundMaternal dietary intervention utilizing complex additives rich in β-carotene has demonstrated the capacity to enhance embryonic intestinal development and influence microbial composition in offspring. Nevertheless, the extended impact of maternal β-carotene inclusion on the intestinal health of post-hatching chicks is still not fully elucidated.ObjectiveThis research aimed to evaluate the impacts of maternal β-carotene supplementation on the intestinal development and microbial communities in chicks after hatching.MethodsA total of 1,215 Hy-Line Brown laying hens were divided into three groups, with each group containing five subgroups of 81 hens each. The hens received a basal diet (CON) or diets added with β-carotene at 120 mg/kg (LBC) or 240 mg/kg (HBC). After 6 weeks of dietary intervention, eggs were collected for incubation. Following hatching, 40 male chicks from each group were randomly chosen and evenly distributed into five distinct subgroups. All chicks were then reared on a uniform basal diet for a duration of 6 weeks.ResultsChicks from the LBC group exhibited significantly higher initial body weight, enhanced villus height (VH), greater villus height to crypt depth ratio (VCR), higher goblet cell (GC) density, and elevated expression of Mucin 2 (MUC2), zonula occludens-1 (ZO1), and zonula occludens-2 (ZO2) in both the jejunum and ileum at 42 days of age. In addition, maternal inclusion of β-carotene 240 mg/kg markedly improved VCR in the jejunum and ileum of chicks. In spite of the observed enhancements in intestinal health, there were no notable variations in overall growth performance across the groups during days 1 to 42. Beta diversity analysis revealed distinct microbial clustering in the ileum of both LBC and HBC groups, clearly separated from the CON group. Taxonomic profiling showed an enrichment of Marivita, Burkholderia, and Turicibacter in the CON group; Oxalobacteraceae, Anoxybacillus, Roseburia, and Anaerorhabdus in the LBC group; and SMB53 and Allobaculum in the HBC group. Correlation analyses indicated positive associations between Anaerorhabdus, Anoxybacillus, and Roseburia and improved intestinal histomorphology, GC abundance, and barrier-related gene expression.ConclusionThese findings suggest that maternal β-carotene addition confers sustained benefits to intestinal health in offspring, potentially mediated by modulation of the cecal microbiome up to day 42.